2007
DOI: 10.1111/j.1742-1241.2007.01491.x
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide to the evaluation and treatment of male lower urinary tract symptoms in the primary care setting

Abstract: Summary Aims:  Lower urinary tract symptoms (LUTS) are common in both men and women, and are among the most prevalent patient complaints heard by primary care physicians (PCPs). This article aims to provide PCPs with a logical algorithm for the assessment and initiation of treatment for LUTS in the male patient. Results:  Management of LUTS involves a focused history and physical, as well as the assessment of bother. In patients for whom treatment is warranted, a series of decisions regarding therapy should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 49 publications
1
64
0
1
Order By: Relevance
“…Firstly, based on the previously reported positive correlation between LUTS and PSA testing, [5][6][7] we reasoned that LUTS would be a factor that is likely to prompt the search for otherwise unsuspected cancers, leading to the detection of localized cancers that would have not been searched for or found in men with no or minimal LUTS. This is a form of verification bias in papers arguing that LUTS should be used to guide decisions on prostate cancer screening, and may explain the results of research showing that LUTS are associated with substantially increased risks of a subsequent prostate cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, based on the previously reported positive correlation between LUTS and PSA testing, [5][6][7] we reasoned that LUTS would be a factor that is likely to prompt the search for otherwise unsuspected cancers, leading to the detection of localized cancers that would have not been searched for or found in men with no or minimal LUTS. This is a form of verification bias in papers arguing that LUTS should be used to guide decisions on prostate cancer screening, and may explain the results of research showing that LUTS are associated with substantially increased risks of a subsequent prostate cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Men with LUTS often worry that their symptoms indicate prostate cancer, 3,4 while a substantial proportion of clinicians perceive an established link between LUTS and prostate cancer 5 and recommend screening for early cancer using the prostate specific antigen (PSA) test in men with urinary symptoms. [5][6][7] Whether screening for early prostate cancer does more good than harm is controversial 8 and the link between LUTS and prostate cancer is unclear. 5 A systematic review of studies to 2000 revealed only 2 directly relevant papers 5 : in a large cohort from the pre-PSA era, recent onset of symptoms was associated with a 4-to 5-fold increased prostate cancer risk 9 ; in contrast, amongst 1,167 men who underwent PSA screening and had a biopsy for a raised PSA level, LUTS were associated with a 30% lower prostate cancer risk.…”
mentioning
confidence: 99%
“…The IPSS is graded from 0 to 35, with general score classifications of 0-7, 8-19 and 20-35, indicating absent or mild, moderate and severe symptoms, respectively. 14,15,16 Patients with a serum PSA level of .10 ng ml 21 were excluded from the study to reduce the likelihood of including those with occult prostate cancer. Patients who had undergone prior biopsies or surgical treatment of prostate disease were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Current guidelines recommend behavioural therapies and lifestyle changes as first line treatments for urinary problems although there is no specific guidance for cancer patients 8, 28. Behavioural techniques include bladder retraining techniques for example progressive voiding schedule together with relaxation and distraction for urinary urgency.…”
Section: Discussionmentioning
confidence: 99%
“…Existing guidance for the management of LUTS in primary care is based on benign prostatic disease 28 and therefore does not take into account the causality and differences in treatment‐related effects from cancer treatment. There is a need for specific guidance to manage LUTS symptoms in the population affected by the spectrum of male pelvic cancers.…”
Section: Introductionmentioning
confidence: 99%